2022
DOI: 10.1088/1741-4326/ac8063
|View full text |Cite
|
Sign up to set email alerts
|

Extended instability of kinetic ballooning modes induced by ion temperature gradient and impurity in tokamaks

Abstract: Kinetic ballooning mode (KBM) instability in tokamak plasmas is studied with gyrokinetic theory. It is extended and improved of the theory of higher order kinetic ballooning mode which is not subject to second stabilization [Hirose A, et al. 1994 Phys. Rev. Lett. 72 3993]. It is verified that increasing ion temperature gradient ($\eta_i$) significantly enhances the instability of KBMs, and causes extended instability in the second MHD stable regime. Especially when $\eta_i\gtrsim 1$, the mode is unstable almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…It is demonstrated that with the increase of magnetic shear ŝ, the critical α for the ideal MHD stable regimes increase. Moreover, when the q value is changed from 2 (the black solid line) to 4 (the green solid line), or when the ŝ value is changed from 1 (the green solid line) to 2 (the blue dasheddotted line) and the other parameters remain unchanged, there is no occurrence of extended instability [25] in both β e and α spaces, but only from one MHD-like ballooning mode to another similar one. That is, from Fig.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is demonstrated that with the increase of magnetic shear ŝ, the critical α for the ideal MHD stable regimes increase. Moreover, when the q value is changed from 2 (the black solid line) to 4 (the green solid line), or when the ŝ value is changed from 1 (the green solid line) to 2 (the blue dasheddotted line) and the other parameters remain unchanged, there is no occurrence of extended instability [25] in both β e and α spaces, but only from one MHD-like ballooning mode to another similar one. That is, from Fig.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…2(b) and (d). In a word, the occurrence of extended instability mainly depends on ion inverse Lamdau damping (when η i ≳ 1 is active) or other causes (e.g., impurity effect (also see [25]).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…为了实现聚变点火目标,建成一个经济、小巧的的受控聚变反应堆,第一步 工作需要实现高𝛽托卡马克稳态运行 [1][2][3][4] 。 这里, 定义 𝛽 = 不稳定性作用,托卡马克所能达到的最大  值是受限的。因此,研究 MHD 不稳定 性成为一个重要课题 [5,6] 。内、外扭曲模是托卡马克中最危险的理想磁流体不稳 定扰动,与先进托卡马克运行的关系非常密切 [7][8][9][10] 。因为与气球模 [11,12] 、撕裂模 [13] 等比较起来,扭曲模对等离子体运行  极限施加了更加严格的限制 [14] 。 一般用归一化等离子体电流来对最大稳定𝛽进行定标,称为 Troyon 定标 [15,16] ,…”
Section: 引言unclassified
“…It is well known that the electrostatic ion temperature gradient (ITG) mode is stabilized by the electromagnetic effects [9,10]. The growth rate of TEM remains unchanged with increasing β e while the electromagnetic kinetic ballooning mode (KBM) becomes unstable when β e exceeds a critical, the growth rate of KBM keeps increasing until β e reaches the second stability region [11,12]. Previous research on KBM mainly focus on those situations with T i ⩾ T e .…”
Section: Introductionmentioning
confidence: 99%